Fiscal Rule and Its Impact on Administrations in Turkey - Mercan, Ayşe; GÜNGÖR, Kamil (Journal of Applied And Theoretical Social Sciences, 2020)
Keynesian thinking was replaced by fiscal rules at the end of the 20th century that set permanent limits on income, spending, budget and borrowing. The aim of these rules is to implement non-numerical rules such as fiscal discipline and fiscal sustainability in developed and developing countries. In our country, fiscal rules began to be applied in 2001, practices were placed on legal grounds, and thus, especially recently, it is seen that primary surpluses have been issued in the central government and local governments. In this study, general information about fiscal rules was given first, and then it was concluded that fiscal rules have a positive effect by focusing on the impact of fiscal rule practices and administrations in the world and Turkey.